Investigating fakes & hoaxes - Woolf, Alex (Chicago, Ill. : Heinemann Library, 2004)
Offers a brief history of forensic science and describes instances in which its techniques have been used to investigate various crimes, including murder, identity theft, and art forgery.
Finding the fakes -- What is forensic science? -- From Aristotle to beta radiography -- Brief history of forensics -- Lost masterpiece? -- Fake Vermeer -- Counterfeit currency -- Howard Hughes hoax -- Hungarian circle -- Hitler diaries -- Framing the neighbor -- Anna or Anastasia -- Stolen identity -- Glossary -- Further reading -- Index.
Keywords: Fraud investigation; Forensic sciences; Criminal investigation